Ruthenium‐Immobilized Periodic Mesoporous Organosilica: Synthesis, Characterization, and Catalytic Application for Selective Oxidation of Alkanes. Issue 44 (14th September 2015) - Ishito, Nobuhiro; Kobayashi, Hirokazu; Nakajima, Kiyotaka; Maegawa, Yoshifumi; Inagaki, Shinji; Hara, Kenji; Fukuoka, Atsushi
Abstract Invited for the cover of this issue is the group of Kenji Hara and Atsushi Fukuoka at Hokkaido University (Japan). The image depicts the catalytic oxidation of alkanes over isolated Ru complexes formed on periodic mesoporous organosilica. Read the full text of the article at 10.1002/chem.201502638.